Efficacy of 20% urea cream on uremic pruritus with uremic xerosis in chronic renal failure patients undergoing hemodialysis - Yulia Farida Yahya; Nina Roiana; Rosi Andarina; Suprapti Suprapti; Irsan Saleh (Faculty of Medicine, Universitas Airlangga, 2018)
Background: Uremic pruritus (UP) is the most common symptoms in patients with chronic renal failure (CRF) undergoing hemodialysis (HD). It is a chronic itch sensation of the skin, with the most frequent clinical manifestation being xerosis, which is difficult to treat. There is a significant relationship between UP and moderate to severe uremic xerosis (UX) in CRF patients undergoing HD. This condition could affect the quality of life and increase the risk of morbidity and mortality. The causes of UP with xerosis are still unclear, however it is evident that there is a disruption of skin barrier function. A 20% urea with the base materials cream consisting sodium pidolat sodium lactate (NaPCA) and vegetable oils that act as a natural moisturizing factor (NMF) can improve the skin barrier function by increasing skin hydration, reducing transepidermal water loss (TEWL) will result in the improvement of UP with UX.